European Society of Cardiology quality indicators for the care and outcomes of adults with heart failure. Developed by the Working Group for Heart Failure Quality Indicators in collaboration with the Heart Failure Association of the European Society of Cardiology. (27th January 2022) - Aktaa, Suleman; Polovina, Marija; Rosano, Giuseppe; Abdin, Amr; Anguita, Manuel; Lainscak, Mitja; Lund, Lars H.; McDonagh, Theresa; Metra, Marco; Mindham, Richard; Piepoli, Massimo; Störk, Stefan; et al.
Abstract: Aims: To develop a suite of quality indicators (QIs) for the evaluation of the quality of care for adults with heart failure (HF). Methods and results: We followed the ESC methodology for QI development, which involved (i) the identification of the key domains of care for the management of HF by constructing a conceptual framework of HF care, (ii) the development of candidate QIs by conducting a systematic review of the literature, (iii) the selection of the final set of QIs using a modified Delphi method, and (iv) the evaluation of the feasibility of the developed QIs. The Working Group comprised experts in HF management including Task Force members of the 2021 European Society of Cardiology (ESC) Clinical Practice Guidelines for HF, members of the Heart Failure Association (HFA), Quality Indicator Committee and a patient representative. In total, 12 main and 4 secondary QIs were selected across five domains of care for the management of HF: (1) structural framework, (2) patient assessment, (3) initial treatment, (4) therapy optimization, and (5) assessment of patient health‐related quality of life. Conclusion: We present the ESC HFA QIs for HF, describe their development process and provide the scientific rationale for their selection. The indicators may be used to quantify and improve adherence to guideline‐recommended clinical practice and thus improve patient outcomes.